2010
DOI: 10.1111/j.1365-2028.2009.01144.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, dynamics and reproduction in a community of small mammals in Upper Guinea, with emphasis on pygmy mice ecology

Abstract: As part of a large survey on reservoirs of Lassa fever in Guinea, three villages were investigated in high endemic zone, close to Sierra Leone border. Biodiversity of the small mammal community is presented in this study through a standardized trapping in houses, cultivations and forest. Identification of the small mammals was based on morphology and by molecular technique for sibling species. Of the 1123 specimens collected in 2003–2005, we identified seventeen species (thirteen Muridae, four Soricidae), lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…Previous studies revealed that at several sites more than one species of Nannomys occurs in sympatry [12,13,23]. Their observations are in agreement with the distribution ranges based on genotyped individuals (Figure 1) showing largely overlapping distribution areas of many species.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies revealed that at several sites more than one species of Nannomys occurs in sympatry [12,13,23]. Their observations are in agreement with the distribution ranges based on genotyped individuals (Figure 1) showing largely overlapping distribution areas of many species.…”
Section: Discussionsupporting
confidence: 88%
“…Only very limited genetic data are available, because the species of the baoulei group are probably rare or difficult to capture [12,13,23]. The species of this group occur in the forest-savannah ecotone and are generally larger than other West African species (except M. setulosus ) [12].…”
Section: Resultsmentioning
confidence: 99%
“…Numerical dominance by very few species is, however, typical of commensal communities (e.g. Fichet-Calvet et al 2010, Shochat et al 2010, Weissbrod et al 2014. We found that species richness varies with latitude with a peak at around 14°N.…”
Section: Consequences Of the House Mouse Invasion For Native Communitmentioning
confidence: 61%
“…In Upper Guinea, M. natalensis comprises between 95% and 98% of rodents captured in houses 20. In coastal Guinea, the black rat Rattus rattus enters into houses and tends to evict M. erythroleucus 21.…”
Section: Introductionmentioning
confidence: 99%